Examining the psychosocial model of sense of presence in the learning management system of e-learning center’s Shahid Beheshti university - soraya khazaei; abbas mohammadi; Mahboobeh Arefi; Esmail Jafari (مجله علوم روانشناختی)
Background: Lack of physical presence in electronic environments is a challenge that includes effects such as the isolation of learners from the instructor and peers, a decreasing in academic satisfaction, and an increasing in school dropouts. A review of recent studies shows that the status of Shahid Beheshti University's e-learning center is not appropriate in terms of the sense of presence; therefore, it is necessary to considering the importance of examining the sense of presence and identifying the aforementioned challenges in order to reduce its adverse effects. Aims: The present study is aimed of providing a model of the sense of presence in the learning management system of e-learning center’s Shahid Beheshti University. Methods: This was a survey-based research. In the first phase, the statistical population included all professors and students of the e-learning center of Shahid Beheshti University and IT specialists in education, who were chosen through judgmental sampling method. In the second phase, the statistical population was the professors and specialists of e-learning courses and PHD candidates who were chosen through convenience sampling method. To collect data, it is used a researcher-made questionnaire tool which its validity was (85%) and its reliability was calculated through calculating Cronbach's alpha coefficient (0.90). At first, the data were analyzed through the one-sample t-test and then, used the AMOS software in the second step. Results: The results showed the average variables of sense of presence (2.416), educational presence (2.663), emotional presence (2.256), cognitive presence (2.263), learning presence (2.472), physical presence (2.340), autonomous presence (2.444) and aesthetic presence (2.319) obtained from the expected average (3) are lower; Therefore, according to the obtained t value and according to the significance level (p< 0.05), the average state of the sense of presence and its dimensions were significantly different from the expected average and were lower than expected. Also, in the second part, the confirmatory factor analysis showed that the identified dimensions included enough factor loading to anticipate the sense of presence in the LMS of Shahid Beheshti University. It didn’t remove the components that included factor loading higher than 0.70 and a significant level equal to p< 0/05 in the total model. Also, the indexes (GFI, NFI, CFI, IFI) with higher value than (0.085) showed that the developed model that related to sense of presence is appropriate in the E-learning environment. The value of RMSEA (0.083) showed the appropriate model Fit. In general, the results of indexes showed the appropriateness of the model. Conclusion: Based on the results of this study, the average state of the sense of presence and its dimensions has a significant difference from the expected average and is lower than expected. This model showed that it can be a suitable model for creating a sense of presence and progress in electronic education. Also, conductiing the more studies with larger sample size could be helpful.